2022
DOI: 10.1101/2022.11.25.517908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel TGF-β-responsive enhancer regulates SRC expression and epithelial–mesenchymal transition-associated cell migration

Abstract: The non-receptor tyrosine kinase SRC is overexpressed and/or hyperactivated in various human cancers, and facilitates cancer progression by promoting invasion and metastasis. However, the mechanisms underlying SRC upregulation are poorly understood. In this study, we demonstrated that transforming growth factor-β (TGF-β) induces SRC expression at the transcriptional level by activating a novel intragenic SRC enhancer. In the human breast epithelial cell line MCF10A and triple-negative breast cancer cell line B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…3.7 KMT2A silencing reversed the TGF-β-induced EMT of ovarian cancer TGF-β is a major inducer in EMT process and tumor cell progression [10,13]. TGF-β-induced EMT is accompanied by the acquisition of mesenchymal markers such as Vimentin, and the loss of epithelial surface markers, notable as E-cadherin [10]. Here, we treated SKOV3 and HO-8910 cells with either control siRNA or KMT2A speci c siRNA, then we stimulated the cells with or without 10ng/ml TGF-β1 for 72h, we found that KMT2A expression was increased after treatment with TGF-β1, but in KMT2A knockdown SKOV3 and HO-8910 cells, TGF-β had no signi cant effect on increase of KMT2A expression (Figs.…”
Section: Kmt2a Was Closely Related To the Emt Process Of Ovarian Cancermentioning
confidence: 96%
See 2 more Smart Citations
“…3.7 KMT2A silencing reversed the TGF-β-induced EMT of ovarian cancer TGF-β is a major inducer in EMT process and tumor cell progression [10,13]. TGF-β-induced EMT is accompanied by the acquisition of mesenchymal markers such as Vimentin, and the loss of epithelial surface markers, notable as E-cadherin [10]. Here, we treated SKOV3 and HO-8910 cells with either control siRNA or KMT2A speci c siRNA, then we stimulated the cells with or without 10ng/ml TGF-β1 for 72h, we found that KMT2A expression was increased after treatment with TGF-β1, but in KMT2A knockdown SKOV3 and HO-8910 cells, TGF-β had no signi cant effect on increase of KMT2A expression (Figs.…”
Section: Kmt2a Was Closely Related To the Emt Process Of Ovarian Cancermentioning
confidence: 96%
“…3.7 KMT2A silencing reversed the TGF-β-induced EMT of ovarian cancer TGF-β is a major inducer in EMT process and tumor cell progression [10,13]. TGF-β-induced EMT is accompanied by the acquisition of mesenchymal markers such as Vimentin, and the loss of epithelial surface markers, notable as E-cadherin [10].…”
Section: Kmt2a Was Closely Related To the Emt Process Of Ovarian Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…Delayed-phase STAT3 phosphorylation (later than 2 h after stimulation) is dependent on Smad3 ( 12 ). c-Src transcriptionally induced by Smad signaling plays a role in the late phase of activation ( 18 ). Because many cell responses induced by TGF-β are Smad dependent, the involvement of non-Smad pathways in the regulation of cellular functions is not well understood.…”
Section: Smad-dependent and Non-smad Pathways In Tgf-β Signalingmentioning
confidence: 99%